Analisis Pengaruh Penambahan Belerang pada Aspal AC-WC terhadap Nilai Stabilitas dan Kelelahan Marshall - Marwan Lubis; Ahmad Bima Nusa; Surya Wenny (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Asphalt concrete as a material for road construction has long been known and is widely used in road construction. This research analysis is to evaluate the effect of adding sulfur to AC-WC asphalt on Marshall stability and fatigue values. Marshall stability and fatigue are key parameters in evaluating asphalt mix quality. Marshall fatigue measures a mixture's ability to overcome fatigue under repeated loading. The initial stage of the research, which was carried out in the engineering laboratory at the Islamic University of North Sumatra, was collecting data and checking the quality of the asphalt material and the quality of the aggregate that would be used in the mixture experiment. The asphalt used consists of oil asphalt, oil asphalt is taken from PT. Adhi Karya Patumbakk, Deli Serdang. The asphalt used in this research was Pertamina asphalt with penetration 60/70 and Esso asphalt with penetration 60/70.1. For a 5% variation, the Stability value was 162 kg, Bulk Density 2.20 gr/cc, flow 2.40 mm, VFA 62.67%, VIM 1.68%, and VMA 16.34%. 2. For a variation of 7%, the Stability value is 175 kg, Bulk Density 2.22 gr/cc, flow 2.61 mm, VFA 75.10%, VIM 1.47%, and VMA 16.36%. 3. For a variation of 9%, Stability is 192 kg, Bulk Density is 2.25 gr/cc, flow is 3.44 mm, VFA is 91.72%, VIM is 2.16%, and VMA is 15.70%. 4. For the Normal variation, you get Stability 204 kg, Bulk Density 2.23 gr/cc, flow 3.60 mm, VFA 71.47%, VIM 3.46%, and VMA 16.99%. 1. From testing the marshall characteristics of the LASTON AC-WC mixture which uses sulfur as an added ingredient with variations of 5%, 7% and 9% with reference to the Bina Marga standard specifications, 2018.